Analysis of the relationship between feeding patterns and the risk of stunting in toddlers at Piyungan Health Center, Bantul - Ulfa, Fitriatul; Kurniawati, Herlin Fitriana (Journal of Nutrition and Public Health, 2025)
Background: Stunting remains a critical public health issue in Indonesia, especially among children under five, due to chronic nutritional deficiencies. Inadequate feeding practices in early childhood are one of the primary contributing factors. Despite existing health interventions, behavioral determinants such as feeding patterns remain underexplored, particularly in rural communities with unique sociocultural dynamics. Aims: This study aims to analyze the relationship between feeding patterns and the incidence of stunting among children aged 1–5 years in the working area of Puskesmas Piyungan, Bantul, Yogyakarta. Methods: A correlational study design with a cross-sectional approach was adopted. Data were collected from 32 purposively selected mother-child dyads from three community health posts. Feeding patterns were assessed through a validated structured questionnaire, and child height was measured using a microtoise. Chi-square tests were applied to examine associations between variables. Results: The study revealed that 83.3% of children with good feeding patterns had normal nutritional status, while 90% of those with poor feeding patterns were stunted. Statistical analysis indicated a significant relationship between feeding patterns and stunting incidence (p = 0.002). Conclusion: The findings underscore the significant influence of maternal feeding behavior on child nutritional outcomes. Improved feeding practices were strongly associated with normal growth, whereas inadequate feeding correlated with high stunting rates. This study advocates for family-centered nutrition education and the reinforcement of community health services, particularly through Posyandu, as strategic measures to combat stunting. The insights contribute to evidence-based policymaking and can inform the design of targeted interventions addressing behavioral causes of malnutrition. Future research with larger samples and longitudinal designs is recommended to evaluate long-term effects and support sustainable nutritional development programs.